Revitalization of Green Open Space (GOS) in Kota Malang as the Government Response to Urban Social Sustainability - Estu Kurniawati, Dyah; Socio Justicia, Jalan; Nur Kusumaningrum, Demeiati; Puspa Haffsari, Peggy (IJRDO - Journal of Social Science and Humanities Research, 2017)
Social sustainability means a policy to create a long-term environment well-being to accommodate communication, interaction, social integration, and public health as the further improvements on quality of life for all segments of the society. The revitalization of Green Open Space (GOS) in Malang City represents the internalization of global ideas toward sustainable urban development paradigm through green city concept. The governmentcorporate partnerships by CSR program successfully promote several thematic innovations and increase the social merits of Green Open Space of Malang City. It results the achievement of the best practice of East Asian green city model in 2015